MELAWAN STIGMA IBU TIRI: KAJIAN SOSIOLOGI SASTRA TERHADAP NOVEL A THOUSAND SPLENDID SUNS KARYA KHALED HOSSEINI - Eva Fatimah (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2016)
The objective of this research is to reveal the stepmother stigma inA Thousand Splendid Suns novel. The analysis of this research usessociological perspective and theory of family sociology by William Goode.The result of the analysis reveals that stepmother can fulfill the socialfunction of a family such as socializing function, social status function,motivational function, and behavioral function. It can be concluded that thenovel were written to oppose stepmother stigma.Keywords: Stepmother, Stigma, Family Social Functio